Pengaruh Dosis Pupuk NPK Terhadap Pertumbuhan Vegetatif Tanaman Cabai Rawit (Capsicum frutescens L.) di Tanah Marginal - Nurul Chairiyah; Aditya Murtilaksono; Muh. Adiwena; Risman Fratama (Universitas Respati Indonesia, 2022)
Cayenne pepper is known as one of main commodities which is often used as food seasoning in Indonesia. The growth of cayenne pepper plant is strongly influenced by fertilizer application. It is because the addition of fertilizer will increase the productivity of cayenne pepper. This research had aim to determine the effect of NPK fertilizer dosage on cayenne pepper vegetative growth at marginal field. This study used a non-factorial randomized block design (RAK) with 5 replications. The treatments were conducted i.e. P0 = Control, P1 = 2.5 grams of NPK, P2 = 5 grams of NPK, P3 = 7.5 grams of NPK, and P4 = 10 grams of NPK. Parameters were observed i.e. plant height, stem diameter, number of leaves, leaf width, leaf length and number of flowers. The data were analyzed using ANOVA, then it were continued with DMRT test. The results showed that the dose of NPK fertilizer had a significant effect in line with the increase in the dose of NPK on the vegetative growth of cayenne pepper plants. The Application of NPK fertilizer 10 grams on plant height was 29.37% higher than without treatment. The Application of NPK fertilizer 10 grams on plant stem diameters was 25.86% wider than it was without treatment. The Application of NPK fertilizer 10 grams on the number of leaves was 36.89% more than it was without treatment. The Application of NPK fertilizer 10 grams on leaf width was 16.25% wider than it was without treatment. The Application of NPK fertilizer 10 grams on leaf length was 23.97% longer than it was without treatment. The Application of NPK fertilizer 10 grams on the number of flowers was 90.93% more than it was without treatment. The P4 treatment, i.e. the application of NPK fertilizer 10 grams, was the best treatment for all vegetative growth parameters of cayenne pepper plants.